Predictors of Progression Among Low-Risk Intraductal Papillary Mucinous Neoplasms in a Multicenter Surveillance Cohort. Issue 4 (April 2018) - Gausman, Valerie; Kandel, Pujan; Van Riet, Priscilla A.; Moris, Maria; Kayal, Maia; Do, Catherine; Poneros, John M.; Sethi, Amrita; Gress, Frank G.; Schrope, Beth A.; Luk, Lyndon; Hecht, Elizabeth; et al.
Abstract : Objectives: Our aim was to identify baseline characteristics associated with disease progression and malignant transformation in low-risk suspected intraductal papillary mucinous neoplasms (IPMNs). Methods: This is a retrospective cohort study of prospectively maintained databases of pancreatic cysts at 3 international, academic institutions. Five hundred fifty-nine adult patients with clinically suspected asymptomatic IPMN evaluated by radiologic studies or endoscopic ultrasound between 2003 and 2013 without worrisome features and under surveillance for 12 months or longer were included. We evaluated the relationship of baseline demographics and cyst features to disease progression (size increase, development of worrisome features, or high-grade dysplasia/cancer). Results: After a median of 44 months follow-up, 269 (48%) patients experienced cyst size increase, 68 (12%) developed worrisome features, and 11 (2%) developed high-grade dysplasia/cancer. In multivariable Cox-regression analysis, no baseline characteristics were associated with size increase. An initial cyst size of 2 cm or greater, multifocality, history of prostate cancer, and smoking were the strongest predictors of development of new worrisome features. Univariable analysis found male sex, diabetes, and recent weight loss associated with development of high-grade dysplasia/cancer. Conclusions: Our study demonstrates that low-risk suspected IPMNs carry a small but clinically relevant risk of disease progression and provides data on baseline characteristics that may help in risk stratification. Abstract : Supplemental digital content is available in the text.